Cellular plasticity facilitates phenotypic change in a dominant coral’s Symbiodiniaceae assemblage - Anthony, Colin J.; Lock, Colin; Taylor, Brett M.; Bentlage, Bastian (Frontiers in Ecology and Evolution, 2023)
Coral-associated dinoflagellates (Symbiodiniaceae) are photosynthetic endosymbionts that influence coral acclimation, as indicated by photo-physiological plasticity (phenotypic variance) in response to environmental change. Symbiont shuffling (shifts in endosymbiont community composition), changes in endosymbiont cell density, and phenotypic plasticity have all been proposed as mechanisms to adjust to environmental change. However, few studies have been able to partition which of the three strategies were responsible for observed phenotypic variance.Using a combination of metabarcoding and flow cytometry, we simultaneously characterized Acropora pulchra-associated Symbiodiniaceae assemblages at the community, population, and individual level under natural environmental conditions to deduce whether seasonal phenotypic change and site-related phenotypic variation of Symbiodiniaceae assemblages is a product of symbiont shuffling or cellular plasticity. Symbiodiniaceae assemblages displayed seasonspecific phenotypic variance, while Symbiodiniaceae community composition was geographically structured and cell density showed limited data structure. Based on these patterns, we reveal that phenotypic plasticity of individual Symbiodiniaceae cells was the source of a phenotypic variation, thus indicating that phenotypic plasticity is a mechanism for acclimation to mild environmental change.